Henryk Zorski (1927-2003), Obituary - Wilmański, K.; Editorial Board, the (Archives of Mechanics, 2004)
Henryk Zorski, Professor of mechanics, a highly respected and very popular member of the international mechanics community passed away on December 26th, 2003. He is survived by his wife, Maria Arcisz, her daughter Krystyna, and his son Krzysztof. His sudden and untimely death yields unfinished his lively research activities on geometrical properties of thermodynamics, on a new approach to statistical mechanics of complex systems and on issues in biomechanics and thermodynamical properties of DNA-chains on which he worked during the recent years.